Supporting students for success in online and distance education - Simpson, Ormond; Simpson, Ormond (New York : Routledge, 2012)
"Supporting Students for Success in Online and Distance Learning, 3rd Edition, provides a comprehensive overview of student support both on and off campus. "--
Rev. ed. of: Supporting students in online, open, and distance learning, c2002.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Distance education; Open learning; Electronic books